Atypical Hemolytic Uremic Syndrome Recurrence after Renal Transplantation: C3-Glomerulonephritis as an Initial Presentation. Issue 2 (March 2015) - Bouatou, Yassine; Bacchi, Véronique Frémeaux; Villard, Jean; Moll, Solange; Martin, Pierre-Yves; Hadaya, Karine
Abstract : Abstract: Risk for atypical hemolytic uremic syndrome (aHUS) recurrence after renal transplantation is low with an isolated membrane cofactor protein mutation ( MCP ). We report the case of a 32-year-old woman with a MCP who underwent kidney transplantation with a good evolution at 12 months. At 15 and 35 months, 2 episodes of thrombotic microangiopathy (TMA), after a miscarriage and a preeclampsia, were misinterpreted as triggered by tacrolimus. After each episode however serum creatinine returned to baseline. Five years after transplantation, she had a self-limited rhinosinusitis followed 3 weeks later by an oliguric renal failure. Her complement profile was normal. Graft biopsy showed C3 glomerulonephritis with no "humps" on electron microscopy. No significant renal function improvement followed methylprednisolone pulsing. A second biopsy showed severe acute TMA lesions with C3 glomerular deposits. Despite weekly eculizumab for 1 month, dialysis was resumed. A new workup identified the "at-risk" complement factor H haplotype. Thus, aHUS recurrence should be ruled out in aHUS patients considered at low recurrence risk when a TMA is found in graft biopsy. Prompt eculizumab therapy should be considered to avoid graft loss as aHUS recurrence can first present as a C3 glomerulonephritis.